THE CONFIGURATION OF LOCAL OLIGARCHY POWER IN EAST KALIMANTAN IN THE COAL MINING SECTOR - Budiman, Budiman; Rohmawati, Tatik; Syarifuddin, Tengku Imam; Jumansyah, Jumansyah; Jefry, Jefry; Valmoria, Junsel James Yongco (CosmoGov: Jurnal Ilmu Pemerintahan, 2026)
The coal mining industry in East Kalimantan has a strategic position in the national economy. It is a field of consolidation of elite power at the local level. This article attempts to study the structure and exercise of local oligarchic power in the coal mining sector in the context of post-reform electoral democracy. This paper adopts a political economy perspective and the concept of oligarchy, understanding oligarchy not only as a wealth-based actor but also as a configuration of power relations within political institutions, bureaucracy, and social networks. The study is qualitative and utilizes a case study in East Kalimantan. Data were gathered by means of in-depth interviews, analysis of policy documents and mining permits, and a search of media reports and civil society organizations. The findings suggest that local oligarchic power is exercised through close integration of regional political elites, capital owners, government bureaucracies, and security actors and is linked to the interests of national elites. Electoral democracy and political decentralization are not mechanisms for restraining oligarchic domination but rather sites for the reproduction and consolidation of elite power. This study demonstrates that weak mining governance and local democratic accountability are the consequences of this institutionalized oligarchic power configuration.